2010
DOI: 10.1021/op1002177
|View full text |Cite
|
Sign up to set email alerts
|

Green Progression for Synthesis of Regioselective β-Amino Alcohols and Chemoselective Alkylated Indoles

Abstract: Solid acid catalysts based on zirconia materials were investigated for the first time as catalysts for regioselective organic synthesis under environmentally benign and mild conditions. The novel TiO2−ZrO2 mixed oxide catalyst led to two distinct products by the formation of an N−C bond (β-amino alcohols) and a C−C bond (Friedel−Crafts alkylation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 53 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…In most cases, the MTF‐1E catalyst is highly efficient, and the reaction proceeded smoothly to afford the desired product β‐amino alcohol in a high isolated yield (89–98 %) within a short reaction time (2–4 h). Styrene oxide underwent ring‐opening if it was reacted with aniline to yield a regioselective product through the preferential attack at the benzylic and more‐hindered terminal carbon atom (Table 2, entry 1) 30f. However, the reaction of aryloxy epoxides and other aliphatic terminal epoxides (epichlorohydrin, allyl glycidyl ether, propylene oxide) with aniline afforded the major secondary alcohol regioisomer regioselectively (Table 2, entries 2–3 and 13–15) through nucleophilic attack at a less sterically hindered carbon atom.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, the MTF‐1E catalyst is highly efficient, and the reaction proceeded smoothly to afford the desired product β‐amino alcohol in a high isolated yield (89–98 %) within a short reaction time (2–4 h). Styrene oxide underwent ring‐opening if it was reacted with aniline to yield a regioselective product through the preferential attack at the benzylic and more‐hindered terminal carbon atom (Table 2, entry 1) 30f. However, the reaction of aryloxy epoxides and other aliphatic terminal epoxides (epichlorohydrin, allyl glycidyl ether, propylene oxide) with aniline afforded the major secondary alcohol regioisomer regioselectively (Table 2, entries 2–3 and 13–15) through nucleophilic attack at a less sterically hindered carbon atom.…”
Section: Resultsmentioning
confidence: 99%
“…The enriched product yields are partly due to the hydrophobic nature of the organic reactants, since their repulsion from water enhances the number of collisions between the organic molecules and increases their ground-state energies, leading to an increase in the reaction rate. 47 In recent years, water has been considered as an excellent reaction medium in synthetic organic chemistry with many promising advantages. Moreover, we have observed that several reactions frequently progress optimally in pure water.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, there are monosubstituent product and disubstituted in well yield under the high pressure and further investigations to develop the reaction epoxides with other nucleophiles in supercritical CO2 or modified supercritical CO2 are now in progress. Reaction in water as solvent: Thirupathi and co-workers reported solid acid catalysts based on zirconia materials for the first time as catalysts for regioselective organic synthesis under environmentally benign and mild conditions in 2010 45 . They tested various solid acids catalysts for the synthesis βamino alcohols and found a novel TiO 2 -ZrO 2 mixed oxide catalyst led to two distinct products by the formation of an N-C bond (β-amino alcohols) (Fig.…”
Section: Asian Journal Of Chemistry Asian Journal Of Chemistrymentioning
confidence: 99%